A catalyst with fly ash as carrier, its preparation method and application

CN117899908BActive Publication Date: 2026-11-03GUODIAN TAIZHOU LONGYUAN ENVIRONMENTAL PROTECTION CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311635001.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-30
Publication Date
2026-11-03
Estimated Expiration
2043-11-30

AI Technical Summary

Technical Problem

Existing technologies have low resource utilization rates for fly ash, and the traditional Fenton oxidation process has a narrow pH range, ineffective H2O2 decomposition, and sludge treatment problems have not been effectively solved.

Method used

Using fly ash as a carrier, a copper-aluminum bimetallic oxide catalyst doped with nitrogen is loaded. Through the galvanic cell effect between copper and aluminum metals and the active sites of the doped copper-N, the utilization efficiency of H2O2 is improved, the applicable pH range is expanded, and sludge production is reduced.

Benefits of technology

It achieves highly efficient catalytic treatment of organic wastewater, efficiently degrades pollutants within a wide pH range, reduces sludge production, and effectively utilizes solid waste fly ash.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117899908B_ABST
    Figure CN117899908B_ABST
Patent Text Reader

Abstract

The present application relates to solid waste disposal and catalyst field, disclose a kind of catalyst with fly ash as carrier and its preparation method and application, the catalyst includes carrier and active component supported on carrier;The carrier is fly ash, and the active component is N-doped copper aluminum bimetallic oxide.The method for preparing the catalyst includes the following steps: (1) copper salt, aluminum salt, nitrogen-containing heterocyclic compound, fly ash and water are mixed and then reacted;(2) the material obtained in step (1) is subjected to solid-liquid separation, and then the solid product is calcined.The catalyst with fly ash as carrier has high catalytic efficiency, wide pH range for treating organic wastewater, and reduces sludge generation during treatment, effectively utilizes solid waste fly ash, and is beneficial to environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid waste treatment and catalyst technology, specifically to a catalyst using fly ash as a carrier, its preparation method, and its application. Background Technology

[0002] In recent years, the resource utilization of fly ash has attracted increasing attention. Recycling fly ash and turning it from waste into treasure is a very meaningful endeavor for reducing environmental pollution. Currently, research on the resource utilization of fly ash in my country is still in its early stages, mainly focusing on building materials, road construction, and agriculture. High-value-added applications of fly ash are still relatively few. To improve the utilization rate of fly ash and achieve high-value-added applications, it is necessary to start from the composition, structure, and properties of fly ash and expand its applications in other fields.

[0003] The traditional Fenton oxidation process is a commonly used technology for treating organic wastewater. However, this process has several problems, such as a narrow applicable pH range, ineffective decomposition of H2O2, and the disposal of sludge generated during the reaction. Among these, the treatment of iron sludge has become a bottleneck restricting the practical application of Fenton technology. Due to the significant limitations of the traditional Fenton reaction, researchers have proposed using transition metals and their oxides to replace Fe. 2+ Fly ash undergoes a Fenton-like reaction with H₂O₂, immobilizing transition metals or other active components on the surface or inside the pores of the support. This not only reduces the loss of active components and maintains the catalyst's activity but also effectively reduces the formation of iron sludge that occurs in traditional Fenton reactions. Currently, fly ash is generally used as an adsorbent for organic wastewater treatment, but this method does not fully utilize its potential. Summary of the Invention

[0004] The purpose of this invention is to overcome the problems existing in the prior art, such as the narrow pH range of solid waste fly ash disposal and organic wastewater treatment, the ineffective decomposition of H2O2, and the generation of sludge during the treatment process. This invention provides a catalyst with fly ash as a carrier, which has high catalytic efficiency, a wide pH range applicable to organic wastewater, and reduces the generation of sludge during the treatment process, while also effectively utilizing solid waste fly ash.

[0005] To achieve the above objectives, the present invention provides a catalyst using fly ash as a support, characterized in that the catalyst comprises a support and an active component supported on the support;

[0006] The carrier is fly ash, and the active component is N-doped copper-aluminum bimetallic oxide.

[0007] A second aspect of the present invention provides a method for using the above-mentioned catalyst supported on fly ash, the method comprising the following steps:

[0008] (1) Mix copper salts, aluminum salts, nitrogen-containing heterocyclic compounds, fly ash and water and then react them;

[0009] (2) The material obtained in step (1) is subjected to solid-liquid separation, and then the solid product is calcined.

[0010] Preferably, in step (1), the molar ratio of copper salt to aluminum salt, calculated as metal, is 4-6:5.

[0011] Preferably, in step (1), the weight ratio of copper salt to nitrogen-containing heterocyclic compound is 1:1-2.5, wherein the copper salt is calculated as a metal.

[0012] Preferably, the nitrogen-containing heterocyclic compound is selected from 2,1,3-benzothiadiazole or dimethylimidazole.

[0013] Preferably, in step (1), the weight ratio of copper salt to fly ash is 1:2-8, wherein the copper salt is calculated as metal.

[0014] Preferably, in step (1), the reaction conditions include: a temperature of 15-25°C and a time of 20-24h.

[0015] Preferably, in step (1), the particle size of fly ash is ≤75 mesh.

[0016] Preferably, step (1) further includes pretreating the fly ash with an acidic solution.

[0017] Preferably, in step (2), the calcination conditions include: a temperature of 400-500℃ and a time of 2-6h.

[0018] A third aspect of the present invention provides a catalyst with fly ash as a support prepared by the above method.

[0019] The fourth aspect of this invention provides the application of the above-mentioned catalyst with fly ash as a carrier in organic wastewater.

[0020] The fifth aspect of the present invention provides a method for treating organic wastewater, the method comprising mixing hydrogen peroxide with organic wastewater in the presence of the catalyst supported by fly ash.

[0021] Preferably, the pH value of the organic wastewater is 3-11.

[0022] Compared with the prior art, the technical solution of the present invention has the following advantages:

[0023] (1) The catalyst with fly ash as a carrier described in this invention exhibits high catalytic efficiency when treating organic wastewater in the presence of hydrogen peroxide. This is because the galvanic cell effect between copper and aluminum metals induces the electronic polarization distribution of the system, thereby forming electron-rich copper centers and electron-deficient aluminum centers. H2O2 can undergo a reduction reaction at the electron-rich copper sites to produce ·OH, thus avoiding the oxidation reaction of H2O2 to produce O2, which cannot directly degrade pollutants, thereby improving the utilization efficiency of H2O2. At the same time, the N atoms doped in the copper-aluminum bimetallic oxide can coordinate with the copper sites to form copper-N active sites. As the element with the highest standard electrode potential in the active sites, N can reduce the density of the electron cloud around the copper sites, thereby promoting the formation of ligand complexes between pollutants and catalysts, and thus increasing the rate of charge transfer from pollutants to catalysts in the system. Furthermore, N in the copper-N active sites can adsorb pollutants through electrostatic force during the reaction, thereby increasing the contact opportunities between pollutants and H2O2, and thus improving the degradation rate of pollutants.

[0024] (2) The catalyst with fly ash as a carrier described in this invention has a wide applicable pH range when treating organic wastewater in the presence of hydrogen peroxide, specifically a pH range of 3-11, and also reduces the generation of sludge during the treatment process.

[0025] (3) The method described in this invention can effectively dispose of solid waste fly ash, which is beneficial to environmental protection. At the same time, the method is simple and efficient. Attached Figure Description

[0026] Figure 1 The image shows the XRD pattern of the catalyst with fly ash as a support prepared in Example 1.

[0027] Figure 2 This is a BET characterization diagram of the catalyst prepared in Example 1 using fly ash as a support;

[0028] Figure 3 This is a scanning electron microscope image of the catalyst with fly ash as a support prepared in Example 1;

[0029] Figure 4 This is the EDS energy dispersive spectroscopy (EDS) analysis diagram of the fly ash-supported catalyst prepared in Example 1.

[0030] Figure 5 The graphs show the removal rates of bisphenol A at different times in reaction systems 1, 2, and 3 for the catalyst with fly ash as a support prepared in Example 1 and the catalysts prepared in Comparative Examples 1 and 2.

[0031] Figure 6 This is a graph showing the removal rate of bisphenol A at different pH values ​​and times in reaction system 1 for the catalyst with fly ash as a carrier prepared in Example 1. Detailed Implementation

[0032] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.

[0033] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0034] The present invention provides a catalyst using fly ash as a support, characterized in that the catalyst comprises a support and an active component supported on the support;

[0035] The carrier is fly ash, and the active component is N-doped copper-aluminum bimetallic oxide.

[0036] A second aspect of the present invention provides a method for using the above-mentioned catalyst supported on fly ash, the method comprising the following steps:

[0037] (1) Mix copper salts, aluminum salts, nitrogen-containing heterocyclic compounds, fly ash and water and then react them;

[0038] (2) The intermediate product obtained in step (1) is subjected to solid-liquid separation, and then the solid product is calcined.

[0039] In this invention, there are no special requirements for the copper and aluminum salts; any salt conventionally used in the art may be selected. For example, the copper salt may be selected from copper sulfate, copper chloride, copper nitrate, copper sulfate hydrate, copper chloride hydrate, or copper nitrate hydrate; the aluminum salt may be selected from aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum sulfate hydrate, aluminum chloride hydrate, or aluminum nitrate hydrate.

[0040] In a preferred embodiment, in order to improve the stability of the copper-aluminum bimetallic oxide, in step (1), the molar ratio of copper salt to aluminum salt, calculated as metal, is 4-6:5; specifically, it can be 4:5, 4.5:5, 5:5, 5.5:5 or 6:5.

[0041] In a preferred embodiment, in order to improve the active sites of the catalyst and thus improve the catalytic activity of the catalyst, in step (1), the weight ratio of copper salt to nitrogen-containing heterocyclic compound is 1:1-2.5, wherein the copper salt is calculated as metal; specifically, it can be 1:1, 1:1.3, 1:1.5, 1:1.7, 1:2, 1:2.3 or 1:2.5.

[0042] In a preferred embodiment, the nitrogen-containing heterocyclic compound is selected from 2,1,3-benzothiadiazole or dimethylimidazole.

[0043] In a preferred embodiment, in order to further improve the catalytic activity of the catalyst, in step (1), the weight ratio of copper salt to fly ash is 1:2-8, wherein the copper salt is calculated as metal; specifically, it can be 1:2, 1:3, 1:4, 1:4.5, 1:5, 1:6, 1:7, 1:7.5 or 1:8.

[0044] In a preferred embodiment, the reaction conditions in step (1) include: a temperature of 15-25°C and a time of 20-24h; the specific temperature can be 15°C, 20°C or 25°C; and the time can be 20h, 21h, 22h, 23h or 24h.

[0045] In a preferred embodiment, in order to better load the N-doped copper-aluminum bimetallic oxide onto the fly ash and thereby improve the catalytic activity, in step (1), the particle size of the fly ash is ≤75 mesh.

[0046] In a preferred embodiment, in order to improve catalytic activity, step (1) further includes pretreating the fly ash with an acidic solution to remove impurities contained in the fly ash, increase the specific surface area and pore size of the fly ash, and facilitate the adsorption of pollutants.

[0047] In a specific implementation, fly ash is pretreated by soaking it in an acidic solution.

[0048] In this invention, there are no special requirements for the acidic solution; any inorganic acid commonly used in the art can be used. For example, it can be hydrochloric acid and / or sulfuric acid.

[0049] In a specific implementation, in order to make the reaction more complete and the N-doped copper-aluminum bimetallic oxide more uniformly loaded on the fly ash, the process of step (1) is as follows: first, copper salt, aluminum salt, nitrogen-containing heterocyclic compound and water are mixed, and then fly ash soaked in acidic solution is added.

[0050] In a specific implementation, in step (2), the material obtained in step (1) is separated into solid and liquid by centrifugation, the solid material is washed with deionized water, the washed sample is placed in an oven for drying, and then calcined and cooled to room temperature.

[0051] In a preferred embodiment, the drying conditions include a temperature of 100-120°C and a time of 12-16 hours.

[0052] In a preferred embodiment, the calcination is carried out in a muffle furnace, and the calcination conditions include: a temperature of 400-500℃ and a time of 2-6 hours; specifically, the temperature can be 400℃, 450℃, or 500℃; and the time can be 2 hours, 3 hours, 4 hours, 5 hours, or 6 hours.

[0053] A third aspect of the present invention provides a catalyst with fly ash as a support prepared by the above method.

[0054] The fly ash-supported catalyst prepared by the above method exhibits high catalytic efficiency when treating organic wastewater in the presence of hydrogen peroxide. This may be due to the galvanic cell effect between copper and aluminum metals inducing electronic polarization distribution in the system, resulting in electron-rich copper centers and electron-deficient aluminum centers. H2O2 can undergo reduction at the electron-rich copper sites to produce ·OH, thus avoiding oxidation of H2O2 to produce O2, which cannot directly degrade pollutants, thereby improving the utilization efficiency of H2O2. Simultaneously, the N atoms doped in the copper-aluminum bimetallic oxide can coordinate with copper sites to form copper-N active sites. As the element with the highest standard electrode potential among the active sites, N can reduce the electron cloud density around the copper sites, thereby promoting the formation of ligand complexes between pollutants and the catalyst, and further increasing the rate of charge transfer from pollutants to the catalyst within the system. Furthermore, N in the copper-N active sites can electrostatically adsorb pollutants during the reaction, increasing the contact opportunities between pollutants and H2O2, and thus improving the degradation rate of pollutants.

[0055] The fourth aspect of the present invention provides the application of the above-mentioned fly ash-supported catalyst in organic wastewater.

[0056] The fifth aspect of the present invention provides a method for treating organic wastewater, the method comprising mixing hydrogen peroxide with organic wastewater in the presence of the catalyst supported by fly ash.

[0057] In a preferred embodiment, to further improve catalytic efficiency, the pH value of the organic wastewater is 3-11; specifically, the pH value of the organic wastewater can be 3, 5, 7, 9 or 11.

[0058] In this invention, the organic wastewater refers to conventional organic wastewater in the art.

[0059] The following examples further illustrate the catalyst using fly ash as a carrier, its preparation method, and its application according to the present invention. The examples are implemented based on the technical solution of the present invention, providing detailed implementation methods and specific operating procedures; however, the scope of protection of the present invention is not limited to the following examples. The fly ash used in the following examples and comparative examples is from Liaocheng Power Generation Co., Ltd. of China Energy Investment Corporation. Other experimental materials, unless otherwise specified, are commercially available.

[0060] Example 1

[0061] (1) Soak fly ash (particle size ≤ 75 mesh) in 0.1 mol / L hydrochloric acid solution for 1 h, filter and dry to obtain pretreated fly ash, then add 3.33 g Al2(SO4)3·18H2O and 1.08 g 2,1,3-benzothiadiazole to 100 mL 0.1 mol / L CuSO4·5H2O solution, stir for 30 min to completely dissolve, then add 3 g pretreated fly ash, and stir magnetically at 25 °C for 20 h;

[0062] (2) The material obtained in step (1) is centrifuged to separate solid and liquid phases. The solid phase material is washed with deionized water. The washed material is then transferred to a silica crucible and dried in a 100°C oven for 12 hours. Finally, it is calcined in a preheated muffle furnace at 450°C for 4 hours. After calcination, the sample is cooled to obtain catalyst M1 with fly ash as the carrier.

[0063] Example 2

[0064] (1) Soak fly ash (particle size ≤ 75 mesh) in 0.1 mol / L hydrochloric acid solution for 1 h, filter and dry to obtain pretreated fly ash, then add 3.33 g Al2(SO4)3·18H2O and 1 g 2,1,3-benzothiadiazole to 100 mL 0.08 mol / L CuSO4·5H2O solution, stir for 30 min to completely dissolve, then add 4 g pretreated fly ash, and stir magnetically at room temperature for 20 h;

[0065] (2) The material obtained in step (1) is centrifuged to separate solid and liquid phases. The solid phase material is washed with deionized water. The washed material is then transferred to a silica crucible and dried in a 100°C oven for 12 hours. Finally, it is calcined in a preheated muffle furnace at 400°C for 6 hours. After calcination, the sample is cooled to obtain catalyst M2 with fly ash as the carrier.

[0066] Example 3

[0067] (1) Soak fly ash (particle size ≤ 75 mesh) in 0.1 mol / L hydrochloric acid solution for 1 h, filter and dry to obtain pretreated fly ash, then add 3.33 g Al2(SO4)3·18H2O and 1.33 g 2,1,3-benzothiadiazole to 100 mL 0.12 mol / L CuSO4·5H2O solution and stir for 30 min to completely dissolve it, then add 3.33 g pretreated fly ash and stir magnetically at room temperature for 20 h;

[0068] (2) The material obtained in step (1) is centrifuged to separate solid and liquid phases. The solid phase material is washed with deionized water. The washed material is then transferred to a silica crucible and dried in a 100°C oven for 12 hours. Finally, it is calcined in a preheated muffle furnace at 500°C for 2 hours. After calcination, the sample is cooled to obtain catalyst M3 with fly ash as the carrier.

[0069] Example 4

[0070] (1) Soak fly ash (particle size ≤ 75 mesh) in 0.1 mol / L hydrochloric acid solution for 1 h, filter and dry to obtain pretreated fly ash, then add 3.33 g Al2(SO4)3·18H2O and 1.2 g dimethyl imidazole to 100 mL 0.12 mol / L CuSO4·5H2O solution, stir for 30 min to completely dissolve, then add 3 g pretreated fly ash, and magnetically stir at room temperature for 20 h;

[0071] (2) The material obtained in step (1) is centrifuged to separate solid and liquid phases. The solid phase material is washed with deionized water. The washed material is then transferred to a silica crucible and dried in a 100°C oven for 12 hours. Finally, it is calcined in a preheated muffle furnace at 450°C for 6 hours. After calcination, the sample is cooled to obtain catalyst M4 with fly ash as the carrier.

[0072] Comparative Example 1

[0073] The method of Example 1 was carried out, except that 2,1,3-benzothiadiazole was not added in step (1) to obtain catalyst A1.

[0074] Comparative Example 2

[0075] The method of Example 1 was implemented, except that in step (1), fly ash was not added to obtain catalyst A2.

[0076] Test case

[0077] (1) The sample prepared in Example 1 was characterized. Figure 1 The image shows the XRD pattern of the catalyst with fly ash as a support prepared in Example 1. Figure 2 This is a BET characterization diagram of the catalyst prepared in Example 1 using fly ash as a support. Figure 2 (a) is the nitrogen adsorption-desorption isotherm curve of the catalyst with fly ash as support prepared in Example 1. Figure 2 (b) is a pore size distribution curve of the catalyst with fly ash as support prepared in Example 1; Figure 3 This is a scanning electron microscope (SEM) image of the catalyst with fly ash as a support prepared in Example 1, wherein... Figure 3(a1) is a scanning electron microscope image of the fly ash-supported catalyst prepared in Example 1 at the 1 μm scale. Figure 3 (a2) is a scanning electron microscope image of the catalyst with fly ash as support prepared in Example 1 at a scale of 500 nm. Figure 4 This is an EDS energy dispersive spectroscopy (EDS) analysis chromatogram of the fly ash-supported catalyst prepared in Example 1. Figure 4 (b1) is the Cu elemental EDS energy spectrum analysis diagram of the catalyst with fly ash as support prepared in Example 1. Figure 4 (b2) is the Al elemental EDS energy dispersive spectroscopy analysis diagram of the catalyst with fly ash as support prepared in Example 1. Figure 4 (b3) is the O element EDS energy spectrum analysis diagram of the catalyst with fly ash as support prepared in Example 1. Figure 4 (b4) is the N element EDS energy spectrum analysis diagram of the catalyst with fly ash as support prepared in Example 1;

[0078] Depend on Figure 1 It can be seen that the catalyst prepared in Example 1 with fly ash as the support exhibits diffraction peaks corresponding to the Al2O3 (PDF#75-1863) phase plane at 25.6° (012), 37.2° (208), 43.4° (113), and 52.6° (024), and diffraction peaks corresponding to the CuO (PDF#80-0076) phase plane at 38.6° (111) and 48.9° (-202). This indicates that the catalyst M1 prepared in Example 1 with fly ash as the support successfully synthesized copper-aluminum bimetallic oxides. Figure 2 It can be seen that the nitrogen adsorption-desorption isotherm curve of the catalyst with fly ash as support prepared in Example 1 exhibits a type IV nitrogen adsorption isotherm curve with a type H3 hysteresis loop, indicating that the catalyst with fly ash as support prepared in Example 1 has a mesoporous structure. Furthermore, the pore size distribution of the catalyst with fly ash as support prepared in Example 1 is relatively narrow, mainly concentrated around 3.94 nm. Figure 3 It can be seen that the catalyst prepared in Example 1 with fly ash as the support exhibits a mesoporous structure, consistent with the results of the nitrogen adsorption-desorption isotherm analysis. The mesoporous structure may be due to the release of CO2 and H2O from the catalyst prepared in Example 1 with fly ash as the support during hydrothermal and calcination processes; Figure 4 As can be seen, the EDS energy spectrum analysis of the catalyst with fly ash as support prepared in Example 1 shows that the four elements Cu, Al, O and N are evenly distributed. This also indicates that the copper-aluminum bimetallic oxide was successfully synthesized and that the N element was successfully doped into the copper-aluminum bimetallic oxide.

[0079] (2) The catalytic performance of the samples prepared in the examples and comparative examples was tested according to the following method: Hydrogen peroxide was added to a 50 mg / L bisphenol A solution as reaction system 1; the sample was added to a 50 mg / L bisphenol A solution as reaction system 2; and the sample and hydrogen peroxide were added to a 50 mg / L bisphenol A solution as reaction system 3. After 30 min, the bisphenol A content in the three systems was tested, and the test results are shown in Table 1. Figure 5 The graphs show the removal rates of bisphenol A at different times in reaction systems 1, 2, and 3 for the catalyst with fly ash as a support prepared in Example 1 and the catalysts prepared in Comparative Examples 1 and 2. Figure 6 This is a graph showing the removal rate of bisphenol A (BPA) of the catalyst prepared in Example 1 using fly ash as a support in reaction system 1 at different pH values ​​and times. Figure 6 (a) is a graph showing the removal rate of bisphenol A of the catalyst prepared in Example 1 with fly ash as the carrier at different pH values ​​and times in reaction system 1. Figure 6 (b) is a graph showing the apparent reaction rate constant (k) of bisphenol A at different pH values ​​and times in reaction system 1 for the catalyst with fly ash as the support prepared in Example 1.

[0080] Table 1

[0081]

[0082] As can be seen from the data in Table 1, the catalyst prepared by the present invention with fly ash as the carrier has high catalytic efficiency and fast catalytic rate, and the removal rate of bisphenol A after 30 min of reaction is as high as 85% or more.

[0083] Depend on Figure 5 It can be seen that, without the addition of H2O2, the removal rate of bisphenol A after 30 min of reaction of the catalyst with fly ash as the carrier prepared in Example 1 was 6.1%, indicating that the catalyst with fly ash as the carrier prepared in Example 1 had a small adsorption effect on pollutants. When only H2O2 was added, the removal rate of bisphenol A after 30 min of reaction was 34.3%, indicating that the oxidation capacity of H2O2 was limited in the absence of a catalyst. When both the catalyst with fly ash as the carrier prepared in Example 1 and H2O2 were added, the removal rate of bisphenol A after 30 min of reaction reached more than 90%. However, when comparative example 1 and H2O2 and comparative example 2 and H2O2 were used to remove bisphenol A, the removal rates of bisphenol A after 30 min of reaction were 70% and 65%, respectively.

[0084] Depend on Figure 6(a) It can be seen that, with the simultaneous addition of H2O2 and the fly ash-supported catalyst prepared in Example 1, the removal rate of bisphenol A after 30 min was 89.3% when the pH of the reaction system was 3, and reached a maximum of 92.3% when the pH of the reaction system was 7. Although the removal rate of bisphenol A decreased slightly when the pH of the reaction system was 9 and 11, it still remained at a high level, at 85.2% and 83.2%, respectively. Figure 6 (b) It can be seen that when the pH of the reaction system is 3, k is 0.055 min. -1 (R 2 =0.98), when the pH of the reaction system is 5, k is 0.059 min. -1 (R 2 =0.97), when the pH of the reaction system is 7, k is 0.068 min. -1 (R 2 =0.98), when the pH of the reaction system is 9, k is 0.044 min. -1 (R 2 =0.97), when the pH of the reaction system is 11, k is 0.040 min. -1 (R 2 =0.97), therefore, the catalyst with fly ash as support prepared in Example 1 can maintain good catalytic activity in the pH range of 3-11 of the reaction system.

[0085] In summary, the catalyst with fly ash as a carrier described in this invention has high catalytic efficiency and a wide pH range, exhibiting good catalytic activity within a pH range of 3-11. Furthermore, the use of fly ash as a carrier makes good use of solid waste fly ash, which is of great significance for environmental protection.

[0086] (3) The treatment capacity of the fly ash-supported catalyst prepared in Example 1 on actual coking wastewater was investigated using a wastewater sample from a coking plant in Jinan City, Shandong Province. The influent COD value of the coking wastewater was 1098 mg / L, and the pH value was 7.5. The wastewater sample from the coking plant in Jinan City, Shandong Province was treated with the fly ash-supported catalyst prepared in Example 1 and 130 mg / L of H2O2. The amount of fly ash-supported catalyst prepared in Example 1 was 1 g / L. After 30 min of reaction, the COD value was 282 mg / L, and the removal rate was 74.3%. Compared with the traditional Fenton process, the reaction rate is faster and the removal efficiency is higher (the traditional Fenton process has a reaction time of 2 h and a removal rate of less than 50%).

[0087] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A method for treating organic wastewater, characterized in that, The method involves mixing hydrogen peroxide with organic wastewater in the presence of a catalyst supported on fly ash; The pH value of organic wastewater is 3-11; The catalyst supported on fly ash includes a support and an active component supported on the support. The carrier is fly ash, and the active component is N-doped copper-aluminum bimetallic oxide; The method for preparing the catalyst using fly ash as a support includes the following steps: (1) The copper salt, aluminum salt, nitrogen-containing heterocyclic compound, fly ash and water are mixed and then reacted; (2) The material obtained in step (1) is subjected to solid-liquid separation, and then the solid product is calcined; In step (1), the nitrogen-containing heterocyclic compound is selected from 2,1,3-benzothiadiazole or dimethylimidazole.

2. The method for treating organic wastewater according to claim 1, characterized in that, In step (1), the molar ratio of copper salt to aluminum salt, calculated as metal, is 4-6:

5.

3. The method for treating organic wastewater according to claim 1 or 2, characterized in that, In step (1), the weight ratio of copper salt to nitrogen-containing heterocyclic compound is 1:1-2.5, wherein the copper salt is calculated as a metal.

4. The method for treating organic wastewater according to claim 1 or 2, characterized in that, In step (1), the weight ratio of copper salt and fly ash is 1:2-8, where copper salt is calculated as metal.

5. The method for treating organic wastewater according to claim 1 or 2, characterized in that, In step (1), the reaction conditions include a temperature of 15-25℃ and a time of 20-24h.

6. The method for treating organic wastewater according to claim 1 or 2, characterized in that, In step (1), the particle size of fly ash is ≤75 mesh.

7. The method for treating organic wastewater according to claim 1 or 2, characterized in that, Step (1) also includes pretreating fly ash with an acidic solution.

8. The method for treating organic wastewater according to claim 1, characterized in that, In step (2), the calcination conditions include: a temperature of 400-500℃ and a time of 2-6h.

Citation Information

Patent Citations

  • Preparation method of FeNi-N / Al2O3 / C catalyst, catalyst and application thereof

    CN106362786A

  • Fenton-like catalytic material having double reactive active centers and preparation method thereof

    CN109174163A